Endoscopic Third Ventriculostomy in a Child with Tectal Glioma and Extremely Diminished Prepontine Interval - Elbaroody, Mohammad; Shafiey, Mahmoud Talaat; Moemen, Wally Hesham; El Refaee, Ehab (Asian Journal of Neurosurgery, 2025)
Diminished prepontine interval is a challenging intraoperative finding that creates an additional risk while doing an endoscopic third ventriculostomy (ETV) due to the proximity of the basilar artery to the ventriculostomy site. It is not a contraindication for the procedure especially in patients with thinned floors through which the vascular structures can be easily visualized and it was not proven to be a risk factor for failure of the procedure. Old children with hydrocephalus secondary to tectal glioma have a high chance of successful ETV, thus avoiding shunt dependency. A 12-year-old male patient presented with headache and grade III papilledema, magnetic resonance imaging brain revealed tectal glioma and triventricular hydrocephalus. He underwent a successful ETV despite a challenging intraoperative, extremely diminished prepontine interval. At 1-year follow-up, brain imaging showed a complete resolution of hydrocephalus and stationary course for the tectal glioma. The present case highlights that diminished prepontine interval is not a contraindication for doing ETV unless safety cannot be guaranteed, and it was not proven to be a risk factor for ETV failure. Creating a stoma on the dorsum sellae after palpating the bone or just behind it using blunt fenestration is a safe way especially in the presence of a thinned third ventricle floor with clearly visualized vascular structures.
Keywords: dorsum sellae; endoscopic third ventriculostomy; ETV; hydrocephalus; prepontine interval; tectal glioma